Organisation of Czech exile in Australia between 1948 and 1989 (Theatrum historiae, 2015)
The communist coup in Czechoslovakia in 1948 produced a huge emigration wave to Western Europe, America and, rather surprisingly, Australia. Based upon yet not studied sources from Czech and Australian archives and libraries, the article examines the organisational platforms of Czech exile in Australian cities and regions, the disputes within its central body (Ústředí československých demokratických organizací v Austrálii a na Novém Zélandu) and the disharmony between post-February and post-August refugees over activities and the ultimate goals of exile movement.
Keywords: Australia; exile; Czechoslovakia; exile organisation; exile after 1948; exile after 1968